Estimating Stature Using Handprint Dimensions: A Medico-Legal Investigative Approach (Medical Forum Monthly, 2023)
ABSTRACTObjective: To evaluate the relation of handprint dimensions using various parameters in the stature estimation of the study population in Hyderabad, Pakistan.Study Design: Cross-sectional studyPlace and Duration of Study: This study was conducted at the Isra University, Hyderabad from August 2021 to July 2022.Materials and Methods: Participants of either gender, aged between 20 and 65 years, appeared to be in good health, without any deformity of hands, feet or vertebral columns were picked randomly. Handprints were scanned to measure the length and breadth of the hand, length of the palm and digits while the height of all participants was also measured.Results: A total of 177 participants were picked of which 51.4% were females. The mean age of the male participants was 25.6±4.8 years and the female was 25.3 ± 4.2 years (age range 21-59). The mean of measured stature for males was 170.1±6.32cm (range: 157-195 cm) was significantly higher than that for females 158.04±6.14 cm (range: 146-174) with the (p < 0.05). Measurements of both handprint lengths had a statistically significant largest difference between both sexes (p<0.05).Conclusion: A strong positive relationship between participant’s handprint parameters and stature. While the most dependable single measure for estimating height was the 2nd digit length of the right handprint in men and the handprint length in females for estimating stature in forensic applications.